Self-assembled micromolecule and preparation method thereof, hole transport material and perovskite battery

By designing self-assembled small molecules with extended conjugation planes and enhancing intermolecular interactions, the problem of poor thermal stability of self-assembled films is solved, the hole transport layer and structural stability of perovskite batteries is improved, and the photoelectric conversion is improved efficiency.

CN119241587APending Publication Date: 2025-01-03旗滨新能源发展(深圳)有限责任公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411361781.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Self-assembled membranes in perovskite batteries have poor thermal stability, which leads to molecular fracture, affects battery performance, and limits the development of trans perovskite batteries.

Method used

Design a self-assembled small molecule to prepare hole transport materials with better dipole moments by introducing extended conjugation planes and enhanced intermolecular interactions during the synthesis process to improve the thermal stability of the hole transport layer and the structural stability of perovskite batteries.

Benefits of technology

The thermal stability of the hole transport layer and the structural stability of the perovskite battery are improved, and the charge transport capacity and photoelectric conversion efficiency of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241587A_ABST
    Figure CN119241587A_ABST
Patent Text Reader

Abstract

The invention discloses a self-assembled micromolecule and a preparation method thereof, a hole transport material and a perovskite battery, and belongs to the technical field of perovskite batteries. The self-assembled micromolecule designed and synthesized by the invention is used as a hole transport material for preparing a hole transport layer to be applied to a perovskite battery, so that the interface contact between the hole transport layer and perovskite can be improved, meanwhile, the energy level is more adaptive, efficient and rapid hole extraction is promoted, and the hole transport efficiency is improved. And the thermal stability of the hole transport layer and the structural stability of the perovskite cell device are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite cells, and in particular to a self-assembling small molecule and a preparation method thereof, a hole transport material and a perovskite cell. Background Art

[0002] As a class of amphiphilic organic compounds that can be combined with substrates through chemical adsorption, self-assembled films (SAMs) have become a promising and powerful tool for solving the interface problems of perovskite cells. Self-assembled films (SAMs) can regulate wettability or improve the adhesion between different layers by establishing interactions, and even directly affect the band structure of adjacent layers. At the same time, the characteristics of high hole selectivity, fast hole transfer rate and low interface trap state density have brought great progress to the performance of inverse perovskite cells and stacked solar cells.

[0003] However, compared with conventional polymer and metal oxide hole transport materials, SAM-based perovskite cells exhibit poor thermal stability because the thermal stability of SAM-forming molecules depends largely on their bonding to the selected substrate. Since the bonds between the anchoring group and the molecular spacer group can be broken by temperature-induced desorption, which adversely affects the stability of the perovskite, it also limits the development of trans perovskite cells. Therefore, the preparation of a new type of efficient and stable hole transport layer is of great significance to the development of perovskite cells. Summary of the invention

[0004] The main purpose of the present invention is to provide a self-assembled small molecule and a preparation method, a hole transport material and a perovskite battery, so as to solve the technical problem that the molecules formed by the self-assembled film are prone to breakage and then affect the performance of the perovskite battery.

[0005] To achieve the above object, the present invention provides a self-assembling small molecule, wherein the self-assembling small molecule has the following structural formula:

[0006]

[0007] The present invention also provides a method for preparing the self-assembling small molecule as described above, comprising the following steps:

[0008] Preparation of compound 2: adding compound 1, 1,2-dibromobutane and catalyst 2 to an alkaline solution, heating for reaction to obtain reactant 2, washing and extracting reactant 2 to obtain extract 2, drying and purifying extract 2 to obtain compound 2, wherein compound 1 is 9H-tetrabenzo[a,c,g,i]carbazole;

[0009] Preparation of compound 3: Compound 2 and triethyl phosphite are mixed, and the mixture is heated under reflux to obtain reactant 3, and reactant 3 is crystallized and washed to obtain compound 3;

[0010] Preparation of self-assembling small molecules: dissolving the compound 3 in an organic solvent and adding trimethylsilyl bromide to react to obtain reactant 4, quenching the reaction and removing excess trimethylsilyl bromide and organic solvent, then adding methanol and dripping water until the solution becomes opaque, filtering to obtain a solid substance, and washing and drying the solid substance to obtain a self-assembling small molecule.

[0011] In some embodiments of the present invention, the structural formulas of Compound 1, Compound 2, and Compound 3 are as follows:

[0012]

[0013] In some embodiments of the present invention, in the step of preparing compound 2,

[0014] And / or, the molar ratio of the compound 1 to 1,2-dibromobutane is 1:(15-30);

[0015] and / or, the catalyst 2 comprises tetrabutylammonium bromide;

[0016] and / or, the alkaline solution comprises an aqueous solution of potassium hydroxide;

[0017] And / or, the temperature range of the heating reaction is 70°C to 100°C;

[0018] And / or, the reaction time of the heating reaction is 12h to 24h;

[0019] and / or, the extraction comprises an extractant, the extractant comprising dichloromethane;

[0020] And / or, the purification comprises silica gel column chromatography.

[0021] In some embodiments of the present invention, in the step of preparing compound 3:

[0022] and / or, the molar ratio of the compound 2 to triethyl phosphite is 1:(15-30);

[0023] And / or, the catalyst 3 comprises tetrabutylammonium bromide.

[0024] And / or, the temperature range of the heating reflux reaction is 150° C. to 200° C.;

[0025] And / or, the reaction time of the heating reaction is 14h to 20h;

[0026] and / or, in the crystallization step, adding petroleum ether to the reactant 3;

[0027] And / or, in the washing step, washing is performed with petroleum ether.

[0028] In some embodiments of the present invention, in the step of preparing the self-assembling small molecule:

[0029] The molar ratio of the compound 3 to trimethylsilyl bromide is 1:(10-20);

[0030] And / or, the organic solvent includes at least one of anhydrous 1,4-dioxane, N,N-dimethylformamide, trichloroethane, and tetrahydrofuran;

[0031] And / or, the reaction time is 20 h to 30 h.

[0032] The present invention also provides a hole transport material, which comprises the self-assembled small molecule described above.

[0033] The present invention also provides a perovskite cell, which comprises a composite hole transport layer, and the composite hole transport layer comprises the hole transport material as described above.

[0034] In some embodiments of the present invention, the method for preparing the composite hole transport layer comprises the following steps:

[0035] Dispersing a hole transport material in a solvent to obtain a hole transport material dispersion solution, and coating the hole transport layer precursor solution on a surface of a substrate to form a hole transport layer;

[0036] The self-assembled small molecules described above are dissolved in an organic solvent to obtain a self-assembled small molecule solution, and the self-assembled small molecule solution is coated on the surface of the hole transport layer to obtain the composite hole transport layer.

[0037] In some embodiments of the present invention, the hole transport material includes nickel oxide; and / or the mass concentration of the self-assembled small molecule solution is (0.3-3) mg / mL.

[0038] In some embodiments of the present invention, the hole transport material includes nickel oxide, and the nickel oxide is dispersed in a solvent to obtain a nickel oxide dispersion solution, and the mass concentration of the nickel oxide dispersion solution is (10-60) mg / ml.

[0039] In some embodiments of the present invention, the perovskite cell further comprises a perovskite active layer, and the perovskite active layer is disposed on the surface of the composite hole transport layer.

[0040] In some embodiments of the present invention, the perovskite cell comprises an inverse perovskite cell, and the inverse perovskite cell comprises, from bottom to top, a front electrode layer, a composite hole transport layer, a perovskite active layer, an electron transport layer and a back electrode layer.

[0041] The beneficial effects that can be achieved by the present invention are:

[0042] The self-assembling small molecules designed and synthesized by the present invention have an extended conjugated plane, which improves the electron-donating ability of the main core unit, enhances the interaction between molecules, shows a better dipole moment, and also improves the ability of the material to transport charges. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0044] Figure 1 Schematic diagram of the synthesis process of self-assembling small molecules according to an embodiment of the present invention.

[0045] Figure 2 The current density-voltage curve comparison diagram of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.

[0046] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0047] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] In the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0050] The present invention provides a self-assembling small molecule, and the self-assembling small molecule of the present invention has the following structural formula:

[0051]

[0052] The self-assembling small molecules designed and synthesized by the present invention have an extended conjugated plane, which improves the electron-donating ability of the main core unit, enhances the interaction between molecules, shows a better dipole moment, and also improves the ability of the material to transport charges.

[0053] The present invention also provides a method for preparing the self-assembling small molecule as described above, comprising the following steps:

[0054] Preparation of compound 2: adding compound 1, 1,2-dibromobutane and catalyst 2 to an alkaline solution, heating for reaction to obtain reactant 2, washing and extracting reactant 2 to obtain extract 2, and drying and purifying extract 2 to obtain compound 2, wherein compound 1 is 9H-tetrabenzo[a,c,g,i]carbazole;

[0055] Preparation of compound 3: Compound 2 and triethyl phosphite are mixed, and the mixture is heated under reflux to obtain reactant 3, and reactant 3 is crystallized and washed to obtain compound 3;

[0056] Preparation of self-assembling small molecules: Compound 3 is dissolved in an organic solvent and trimethylsilyl bromide is added to react to obtain reactant 4. After quenching the reaction and removing excess trimethylsilyl bromide and organic solvent, methanol is added and water is added dropwise until the solution becomes opaque. A solid substance is obtained by filtering. The solid substance is washed and dried to obtain a self-assembling small molecule.

[0057] In some embodiments, compound 1 can be purchased from the market, or can be prepared according to the preparation methods disclosed in the art.

[0058] In some embodiments, Compound 1 has the following structural formula:

[0059]

[0060] In some embodiments, compound 2 is prepared by compound 1, and compound 2 has the following structural formula:

[0061]

[0062] In some embodiments, the molar ratio of compound 1 to 1,2-dibromobutane is 1:(15-30), which can be any value within the range of 1:(15-30), such as 1:15, 1:18, 1:20, 1:25, 1:28, 1:30, etc.

[0063] In some embodiments, Catalyst 2 includes tetrabutylammonium bromide.

[0064] In some embodiments, the molar ratio of compound 1 to catalyst 2 is 1:0.2.

[0065] In some embodiments, the reaction vessel for preparing compound 2 includes a reaction tube. For example, compound 1, 1,2-dibromobutane, catalyst 2 and alkaline solution can be added sequentially into the reaction tube and reacted under heating conditions.

[0066] In the present invention, the alkaline solution mainly plays the role of dissolving and dispersing compound 1, 1,2-dibromobutane, and promoting the complete reaction of compound 1, 1,2-dibromobutane. In some embodiments, the alkaline solution includes an aqueous solution of potassium hydroxide.

[0067] In some embodiments, the mass concentration of the alkaline solution is 50%.

[0068] In some embodiments, the temperature range of the heating reaction is 70° C. to 100° C., and can be any value in the range of 70° C. to 100° C., such as 70° C., 80° C., 90° C., 100° C. At the above reaction temperature, it is beneficial to promote the reaction of compound 1 and 1,2-dibromobutane to produce compound 2.

[0069] In some embodiments, the reaction time of the heating reaction is 12 hours to 24 hours.

[0070] In some embodiments, the spot plate reaction can be used to determine the extent of the reaction, and after the reaction is completed, the subsequent washing and extraction steps can be performed.

[0071] In some embodiments, after the heating reaction is completed, the reactant 2 can be cooled to room temperature (25° C. to 30° C.) and then washed with water.

[0072] In some embodiments, the extracting comprises an extractant comprising dichloromethane.

[0073] In the step of preparing compound 2, the purpose of drying is to remove the extractant in the extract 2 to obtain a solid substance. In some embodiments, the extract 2 can be dried using a desiccant, and the desiccant includes anhydrous magnesium sulfate; in some embodiments, the extract 3 can also be evaporated and dried by an evaporation method. For example, the extract 2 is dried using a rotary evaporator; in some embodiments, the extract 2 can also be dried by combining a desiccant and an evaporation method. For example, the extract 2 is dried using a desiccant to remove most of the extractant, and then the residual extractant is evaporated by the evaporation method, which is beneficial to improving the efficiency and effect of drying.

[0074] In some embodiments, purification comprises silica gel column chromatography.

[0075] In some embodiments, the silica gel column chromatography method includes a purification agent, and the purification agent includes a mixture of petroleum ether and dichloromethane.

[0076] In some implementations, the volume ratio of petroleum ether to dichloromethane is 3:1.

[0077] In some embodiments, purification is performed using silica gel column chromatography, and after purification is completed, a drying step is further included to remove the residual purifying agent after purification. Exemplarily, the residual purifying agent can be removed by evaporation, and the evaporation method includes rotary evaporation.

[0078] In some embodiments, compound 3 is prepared by compound 2, and compound 3 has the following structural formula:

[0079]

[0080] In some embodiments, the reaction vessel for preparing compound 3 includes a reaction tube. For example, compound 2 and triethyl phosphite can be added sequentially into the reaction tube to perform a heating reflux reaction.

[0081] In some embodiments, after adding compound 2 and triethyl phosphite into a reaction container, before heating and refluxing, the reaction container is evacuated and nitrogen is introduced several times to exclude air and reduce interference of air on the reaction.

[0082] In some implementations, the heating reflux reaction is carried out in an iron sand bath, which is beneficial to improving the heat transfer effect and promoting a more complete reaction.

[0083] In some embodiments, the molar ratio of compound 2 to triethyl phosphite is 1:(15-30), which can be any value in the range of 1:(15-30), such as 1:15, 1:20, 1:25, 1:30, etc.

[0084] In some embodiments, the temperature range of the heating reflux reaction is 150°C to 200°C, and can be any value within the range of 150°C to 200°C, such as 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc.

[0085] In some embodiments, the reaction time of the heating reaction is 14 h to 20 h.

[0086] In some embodiments, in the crystallization step, petroleum ether is added to reactant 3 to promote the crystallization of reactant 3 to obtain crystals containing compound 3.

[0087] In some embodiments, the crystallization is carried out at -5°C to 10°C.

[0088] In some embodiments, the solid material is obtained by suction filtration after crystallization.

[0089] In some embodiments, the solid material obtained after crystallization is washed to remove impurities to obtain compound 3 in the form of white powder.

[0090] In some embodiments, washing is performed with petroleum ether.

[0091] In some embodiments, the molar ratio of compound 3 to trimethylsilyl bromide is 1:(10-20), and can be any value in the range of 1:(10-20), such as 1:10, 1:13, 1:15, 1:18, 1:20, etc.

[0092] In some embodiments, trimethylsilyl bromide is added dropwise, which is beneficial for controlling the reaction.

[0093] In some embodiments, the organic solvent includes at least one of anhydrous 1,4-dioxane, N,N-dimethylformamide, trichloroethane, and tetrahydrofuran.

[0094] In some embodiments, the reaction can be carried out at room temperature, for example, the reaction temperature can be any value in the range of 20°C to 35°C, such as 20°C, 25°C, 30°C, 35°C.

[0095] In some embodiments, the reaction time is 20 h to 30 h.

[0096] In some implementations, methanol may be added to the obtained reactant 4 to remove excess trimethylsilyl bromide.

[0097] In some embodiments, excess organic solvent may be removed by evaporation.

[0098] In some embodiments, methanol is first added to reactant 4 to remove excess trimethylsilyl bromide, and then excess organic solvent is removed by evaporation.

[0099] The self-assembling small molecule of the present invention is prepared by compound 1, compound 2, and compound 3 in sequence. In one embodiment, reference Figure 1The preparation process of the self-assembling small molecule is as follows: first, compound 1 and 1,2-dibromobutane are dissolved in an aqueous solution of potassium hydroxide, and compound 2 is generated under the catalysis of catalyst tetrabutylammonium bromide (TBAB). Compound 2 and triethyl phosphite react in an aqueous solution of potassium hydroxide under the catalysis of catalyst tetrabutylammonium bromide (TBAB) to generate compound 3, and then compound 3 and trimethylsilyl bromide are dissolved in an organic solvent 1,4-dioxane aqueous solution for reaction, and the final product self-assembling small molecule is obtained by crystallization with the help of methanol. The self-assembling small molecule synthesized in this embodiment has an extended conjugated plane, improves the electron donating ability of the main core unit, enhances the interaction between molecules, shows a better dipole moment, and also improves the ability of the material to transport charge.

[0100] In the related art, SAM-based perovskite cell devices exhibit poor thermal stability compared with conventional polymer and metal oxide hole transport materials, because the thermal stability of SAM-forming molecules largely depends on their bonding to the selected substrate. Since the bonds between the anchoring group and the molecular spacer group can be broken by temperature-induced desorption, the stability of the perovskite is adversely affected, which also limits the development of inverse perovskite cell devices.

[0101] In view of this, the present invention also provides a hole transport material, the hole transport material includes the self-assembled small molecules as described above. The self-assembled small molecules of the present invention are applied to the hole transport layer of the perovskite battery as hole transport materials. The self-assembled small molecules can be anchored to the surface of the hole transport layer and fixed at the interface between the hole transport layer and the perovskite active layer, thereby improving the interface contact between the hole transport layer and the perovskite, while making the energy level more adaptable, promoting efficient and rapid hole extraction, such an interface configuration allows the self-assembled molecules to be firmly fixed at the interface between the hole transport layer and the perovskite, and with the help of the stronger bonding between the self-assembled molecules and the hole transport layer, the thermal stability of the hole transport layer and the structural stability of the perovskite battery device are improved. The above-mentioned hole transport layer can be applied to trans-perovskite batteries, so that the trans-perovskite batteries can obtain better photoelectric conversion efficiency, and provide inspiration and reference for the design and optimization of the hole transport layer structure in the perovskite battery.

[0102] The present invention further provides a perovskite cell, which includes a composite hole transport layer, and the composite hole transport layer includes the hole transport material as described above. The perovskite cell of the present invention has at least all the beneficial effects of the above-mentioned self-assembled small molecules.

[0103] In some embodiments, a method for preparing a composite hole transport layer in a perovskite cell comprises the following steps:

[0104] S10, dispersing a hole transport material in a solvent to obtain a hole transport material dispersion solution, and coating the hole transport layer precursor solution on a surface of a substrate to form a hole transport layer;

[0105] S20, dissolving the self-assembled small molecules described above into an organic solvent to obtain a self-assembled small molecule solution, and coating the self-assembled small molecule solution on the surface of the hole transport layer to obtain the composite hole transport layer.

[0106] In this embodiment, the self-assembled small molecules are anchored on the hole transport layer. The composite hole transport layer prepared by the combination of the hole transport layer and the self-assembled small molecules can improve the interface contact with the perovskite, while making the energy level more adaptable, promoting efficient and rapid hole extraction, and the self-assembled small molecules are fixed at the interface between the hole transport layer and the perovskite active layer. The self-assembled small molecules can be used to strengthen the bonding effect between the hole transport layer and the perovskite active layer, thereby improving the thermal stability of the hole transport layer and the structural stability of the perovskite battery device.

[0107] In this embodiment, the prepared composite hole transport layer can be applied to an inverse perovskite cell, which is beneficial for the perovskite cell to obtain a better photoelectric conversion efficiency, and provides inspiration and reference for the design and optimization of the hole transport layer structure in the perovskite cell. Therefore, in some embodiments, the substrate in step S10 includes a conductive substrate, and the composite hole transport layer is prepared on the surface of the conductive substrate, thereby obtaining an inverse perovskite cell.

[0108] In some embodiments, the substrate is a conductive substrate. Before the hole transport material dispersion solution is applied to the surface of the conductive substrate, the conductive substrate is cleaned, including the following steps: drying the cleaned substrate with a hot air gun and placing it in an ultraviolet ozone treatment machine for ozone treatment, cooling it for standby use. The time of ozone treatment can be determined according to actual conditions and can be 20 minutes.

[0109] In some embodiments, the hole transport material includes nickel oxide, from which a nickel oxide film can be prepared, and the self-assembled small molecules are anchored on the NiOx film. The NiOx / 4PATCB composite hole transport layer is prepared by the combination of NiOx and the self-assembled small molecules. The composite hole transport layer can improve the interfacial contact with the perovskite active layer, while making the energy level more adaptable, promoting efficient and rapid hole extraction. Such an interface configuration also fixes the self-assembled molecules at the interface between NiOx and perovskite, and with the help of the stronger bonding effect between the self-assembled molecules and the nickel oxide layer, the thermal stability of the composite hole transport layer and the structural stability of the perovskite battery device are improved.

[0110] In some embodiments, nickel oxide is dispersed in a solvent to obtain a nickel oxide dispersed solution, and the mass concentration of the nickel oxide dispersed solution is (10-60) mg / ml, for example, it can be any value in the range of (10-60) mg / ml, such as 10 mg / ml, 20 mg / ml, 30 mg / ml, 40 mg / ml, 50 mg / ml, 60 mg / ml, etc.

[0111] In some embodiments, ultrapure water is used as a solvent, and nickel oxide is dispersed in ultrapure water to obtain a nickel oxide dispersed solution.

[0112] In some embodiments, after the nickel oxide is dispersed in the solvent, it may be shaken for 1 to 5 minutes and ultrasonically treated for 10 to 30 minutes to promote uniform dispersion of the nickel oxide, thereby preparing a uniform nickel oxide film layer.

[0113] In some embodiments of step S10, the nickel oxide is further filtered using a 0.45 μm water filter membrane.

[0114] In some embodiments, the mass concentration of the nickel oxide dispersion solution is (10-60) mg / ml, for example, it can be any value in the range of (10-60) mg / ml, such as 10 mg / ml, 20 mg / ml, 30 mg / ml, 40 mg / ml, 50 mg / ml, 60 mg / ml, etc.

[0115] In some embodiments, the substrate is placed on a spin coater under a nitrogen atmosphere, a nickel oxide dispersion solution is dripped onto the surface of the substrate, and the nickel oxide dispersion solution is spin-coated onto the surface of the substrate to form a nickel oxide hole transport layer.

[0116] In some embodiments, the spin coating speed is 3000 rpm, and the spin coating time is 30 s.

[0117] In some embodiments, after the nickel oxide dispersion solution is spin-coated onto the surface of the substrate, an annealing treatment is performed to remove chlorobenzene.

[0118] In some embodiments, the annealing temperature is 150° C. to 200° C., and the annealing time is 20 min to 40 min, including 30 min.

[0119] In some embodiments, after the self-assembling small molecules are dissolved in the organic solvent, they can be shaken to fully dissolve them.

[0120] In some embodiments, the organic solvent comprises ethanol.

[0121] In some embodiments, the mass concentration of the self-assembled small molecule solution is (0.3-3) mg / ml, for example, it can be any value in the range of (0.3-3) mg / ml, such as 0.3 mg / ml, 0.5 mg / ml, 0.8 mg / ml, 1 mg / ml, 1.5 mg / ml, 2 mg / ml, 2.5 mg / ml, 3 mg / ml, etc., thereby strengthening the anchoring of the self-assembled small molecules on the surface of the substrate, strengthening the binding force between adjacent functional layers, and improving the thermal stability of the hole transport layer and the structural stability of the perovskite battery device.

[0122] In some embodiments, on a spin coater in a nitrogen atmosphere, a self-assembled small molecule solution is dripped onto the surface of the nickel oxide film layer, so that the self-assembled small molecules are spin-coated onto the surface of the nickel oxide film layer.

[0123] In some embodiments, the spin coating speed is 3000 rpm, and the spin coating time is 30 s.

[0124] In some embodiments, after the self-assembling small molecule solution is spin-coated onto the surface of the substrate, an annealing treatment is performed to remove residual solvent.

[0125] In some embodiments, the annealing temperature is 100° C., and the annealing time is 20 min to 40 min, including 30 min.

[0126] In some embodiments, the perovskite cell also includes a perovskite active layer, which is disposed on the surface of the composite hole transport layer as described above. The interface contact between the hole transport layer and the perovskite can be improved with the help of self-assembled small molecules, while making the energy level more adaptable and promoting efficient and rapid hole extraction. Such an interface configuration also allows the self-assembled molecules to be fixed at the interface between the hole transport layer, such as the NiOx film layer, and the perovskite active layer. With the help of stronger bonding between the self-assembled molecules and the hole transport layer, the thermal stability of the composite hole transport layer and the structural stability of the perovskite cell device are improved.

[0127] Exemplarily, the perovskite cell includes, from bottom to top, a front electrode layer, the above-mentioned composite hole transport layer, a perovskite active layer, an electron transport layer and a back electrode layer.

[0128] In some embodiments, other functional layers commonly used in the technical field may be provided between the front electrode layer and the hole transport layer, between the perovskite active layer and the electron transport layer, and between the electron transport layer and the back electrode layer in the perovskite cell, which are not limited here.

[0129] In the present invention, the front electrode layer, the titanite light-absorbing layer, the electron transport layer and the back electrode in the perovskite cell can be prepared by conventional technical means in the art.

[0130] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0131] Example 1

[0132] 1. Preparation of self-assembling small molecules

[0133] Prepare compound 1, which is 9H-tetrabenzo[a,c,g,i]carbazole.

[0134] Preparation of compound 2: Compound 1 (1.488 g, 4.05 mmol), 9.7 ml of 1,2-dibromobutane, tetrabutylammonium bromide (260.2 mg, 0.81 mmol) and 2.2 ml of a 50% aqueous solution of potassium hydroxide were added to a 100 ml reaction tube in sequence, and the temperature was raised to 70 ° C. for 12 h. The reaction was determined to be complete by spot plate reaction. After the spot plate reaction was complete, the obtained reactant 2 was cooled to room temperature, washed with water, and then extracted with dichloromethane to obtain extract 2. The extract 2 was then dried over anhydrous magnesium sulfate, and the residual solvent was dried using a rotary evaporator to collect a solid substance, which was purified by silica gel column chromatography (the purifying agent is as follows: the volume ratio of petroleum ether and dichloromethane is 3:1) to obtain compound 2 (1.131 g, 76%).

[0135] Preparation of compound 3: Compound 2 (1.517 g, 3.02 mmol) and 10.4 ml of triethyl phosphite were added to a 100 ml reaction tube, and the air was removed by vacuuming and passing nitrogen several times, and then refluxed in an iron sand bath at 160°C for 16 h to obtain reactant 3. The completion of the reaction was determined by spot plate reaction. After the spot plate reaction was complete, reactant 3 was cooled to room temperature, and 200 ml of petroleum ether was introduced to crystallize at a low temperature of -5 to 10°C, and then filtered to obtain a solid substance, which was washed with petroleum ether to obtain white powder compound 3 (1.229 g, 81%).

[0136] Preparation of self-assembling small molecules: Under a nitrogen atmosphere, compound 3 (1.133 g, 2.25 mmol) was dissolved in anhydrous 1,4-dioxane (15 ml), and trimethylsilyl bromide (3.0 ml, 22.52 mmol) was added dropwise. The reaction was carried out at room temperature for 24 h to obtain reactant 4. Methanol (greater than or equal to 2 ml) was added to the reactant 4 and stirring was continued for 3 h. Then, part of the solvent was removed by rotary evaporation, and 8 ml of methanol was added. Finally, distilled water (15 ml) was added dropwise until the solution became opaque. The solution was stirred overnight (12 h), and the product was filtered out. The product was washed with water and dried to obtain a self-assembling small molecule (0.941 g, 83%). The self-assembling small molecule is represented by 4PATCB.

[0137] 2. Preparation of perovskite cells

[0138] Cleaning of ITO conductive glass

[0139] The ITO conductive glass with the protective film removed was ultrasonically cleaned using deionized water with detergent, and then the ITO conductive glass was ultrasonically treated in deionized water, acetone, and isopropanol in sequence for 20 minutes for use.

[0140] Preparation of composite hole transport layer

[0141] Weigh 10 mg to 60 mg of commercial nickel oxide, disperse it in 1 ml of ultrapure water solution to prepare a nickel oxide solution with a mass concentration of (10 to 60) mg / ml, then oscillate for 1 min to 5 min, and ultrasonically treat for 10 min to 30 min, then filter through a 0.45 μm water filter to obtain a nickel oxide dispersion solution for use.

[0142] Use a hot air gun to dry the cleaned ITO conductive glass and place it in a UV ozone treatment machine for ozone treatment for 20 minutes. Take out the ITO conductive glass and wait for it to cool to room temperature, then place it on a coater under a nitrogen atmosphere in a glove box. Use a pipette to drop 50 μl of nickel oxide dispersion solution and start the spin coating program with a spin coating speed of 3000 rpm and a spin time of 30 seconds. After the spin coating is completed, place it on a hot stage at 150°C to 200°C for 30 minutes of thermal annealing to remove water, and a nickel oxide film layer can be obtained.

[0143] Dissolve 4PATCB in an ethanol solution and shake it to fully dissolve it to obtain a 4PATCB dispersion solution with a concentration of 0.3 to 3 mg / mL. After the ITO conductive glass with a nickel oxide film layer is cooled to room temperature, it is placed on a homopolymer in a nitrogen atmosphere in a glove box, 50 μl of the 4PATCB dispersion solution is added with a pipette, and the spin coating program is started with a spin coating speed of 3000 rpm and a spin time of 30 s. After the spin coating is completed, it is placed on a hot plate at 100°C for 30 minutes of thermal annealing to remove the remaining solvent, and a NiOx / 4PATCB composite hole transport layer is obtained.

[0144] Preparation of perovskite active layer

[0145] A mixture of 19.8 mg CsI, 16.2 mg MABr, 20.3 mg MACl, 224.4 mg FAI, and 742.2 mg PbI2 powders was dissolved in 1 ml of anhydrous DMF / DMSO mixture solvent, with a volume ratio of DMF to DMSO of 4:1, and stirred at 60 °C for 2 h to fully dissolve the mixture to obtain a perovskite precursor solution. The components of the perovskite precursor solution were Cs 0.05 FA 0.85 MA0.1 Pb(I 0.97 Br 0.03 )3, the concentration is 1.61mol / L.

[0146] The perovskite active layer was prepared by a one-step method, with chlorobenzene as the anti-solvent. Specifically, 50 μl of the above perovskite precursor solution was transferred and spin-coated on the surface of the NiOx / 4PATCB composite hole transport layer, and the spin-coating procedure was started. The first spin procedure was a rotation speed of 1000 rpm for 10 s, and the second spin procedure was a rotation speed of 5000 rpm for 30 s. 100 μl of chlorobenzene was added dropwise within 20 to 25 s after the second spin procedure was started. After the spin-coating procedure was completed, the sample was placed on a 150°C hot stage for annealing for 10 min to form a perovskite active layer.

[0147] Preparation of functional layer and metal electrode layer

[0148] In the glove box, the ITO conductive glass with the perovskite active layer prepared was placed in a metal vacuum evaporation chamber, and then -4 Atmospheric pressure, 35nm thick C 60 , 7nm thick 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) and 100nm thick Ag electrode, finally a complete area of ​​0.06cm 2 Perovskite battery devices.

[0149] Comparative Example 1

[0150] The comparative example is prepared by referring to the preparation method of Example 1 to obtain a perovskite battery. The difference is that in the step of preparing the hole transport layer, the self-assembled small molecule prepared in Example 1 is not added in Comparative Example 1, but the hole transport layer is directly prepared using NiOx as a raw material. The structure of the perovskite battery obtained is ITO / NiOx / Cs 0.05 FA 0.85 MA 0.1 Pb(I 0.97 Br 0.03 )3 / C 60 / BCP / Ag.

[0151] Comparative Example 2

[0152] Comparative Example 2: A perovskite cell was prepared by referring to Example 1. The difference is that in the step of preparing the hole transport layer, the self-assembled small molecule of Example 1 was replaced by a commercial SAM material of equal molar mass to prepare a trans-perovskite cell containing a NiOx / 4PADCB composite hole transport layer, and the structure is ITO / NiOx / 4PADCB / Cs 0.05 FA 0.85 MA0.1 Pb(I 0.97 Br 0.03 )3 / C 60 / BCP / Ag.

[0153] Performance Testing

[0154] Under standard sunlight (AM 1.5G), the perovskite cells prepared in Example 1 and Comparative Examples 1 and 2 were tested for device performance. The current density-voltage curve of the perovskite cell is shown in FIG. Figure 1 The measured data are shown in Table 1.

[0155] Table 1

[0156] Experimental Group <![CDATA[Jsc(mA cm -2 )]]> Voc(V) FF(%) PCE(%) Example 1 24.75 1.153 81.83 23.35 Comparative Example 1 22.73 1.065 77.08 18.67 Comparative Example 2 24.27 1.124 81.06 22.12

[0157] The self-assembled small molecules of the present invention are applied to the hole transport layer of the perovskite battery, and the self-assembled small molecules are anchored to the NiOx film to prepare a NiOx / 4PATCB composite hole transport layer, which can improve the interface contact between the hole transport layer and the perovskite, while making the energy level more adaptable, promoting efficient and rapid hole extraction. Such an interface configuration also allows the self-assembled small molecules to be firmly fixed at the NiOx / perovskite interface. With the help of the stronger bonding between the self-assembled small molecules and the nickel oxide layer, the thermal stability of the composite hole transport layer is improved, and the structural stability of the perovskite device is also improved. Figure 1 As shown in Table 1, the open circuit voltage Voc of the perovskite battery reverse scanning device of Example 1 is 1.153V, and the short circuit current is 24.75mA / cm -2 , the filling factor is 81.83%, and the photoelectric conversion efficiency is 23.35%. The results show that NiOx / 4PATCB has great application potential as a composite hole transport material in inverse perovskite battery devices.

[0158] In Comparative Example 1, only NiOx was used to prepare the hole transport layer. The performance of the perovskite battery was greatly reduced, with an open circuit voltage Voc of only 1.065 V and a short circuit current of only 22.73 mA / cm -2 , the filling factor is only 77.03%, and the photoelectric conversion efficiency is only 18.67%.

[0159] In Comparative Example 2, commercial SAM materials were used to replace the self-assembled small molecules of the present invention to prepare the composite hole transport layer, and the performance of the perovskite cell obtained thereby also decreased.

[0160] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A self-assembling small molecule, characterized in that: The self-assembling small molecule has the following structural formula:

2. A method for preparing the self-assembling small molecule according to claim 1, characterized in that: The following steps are involved: Preparation of compound 2: adding compound 1, 1,2-dibromobutane and catalyst 2 to an alkaline solution, heating for reaction to obtain reactant 2, washing and extracting reactant 2 to obtain extract 2, drying and purifying extract 2 to obtain compound 2, wherein compound 1 is 9H-tetrabenzo[a,c,g,i]carbazole; Preparation of compound 3: Compound 2 and triethyl phosphite are mixed, and the mixture is heated under reflux to obtain reactant 3, and reactant 3 is crystallized and washed to obtain compound 3; Preparation of self-assembling small molecules: dissolving the compound 3 in an organic solvent and adding trimethylsilyl bromide to react to obtain reactant 4, quenching the reaction and removing excess trimethylsilyl bromide and organic solvent, then adding methanol and dripping water until the solution is opaque, filtering to obtain a solid substance, and washing and drying the solid substance to obtain a self-assembling small molecule; The structural formulas of Compound 1, Compound 2 and Compound 3 are as follows:

3. The method for preparing the self-assembling small molecule according to claim 2, characterized in that: In the step of preparing compound 2, And / or, the molar ratio of the compound 1 to 1,2-dibromobutane is 1:(15-30); and / or, the catalyst 2 comprises tetrabutylammonium bromide; and / or, the alkaline solution comprises an aqueous solution of potassium hydroxide; And / or, the temperature range of the heating reaction is 70°C to 100°C; And / or, the reaction time of the heating reaction is 12h to 24h; and / or, the extraction comprises an extractant, the extractant comprising dichloromethane; And / or, the purification comprises silica gel column chromatography.

4. The method for preparing the self-assembling small molecule according to claim 2, characterized in that: In the step of preparing compound 3: and / or, the molar ratio of the compound 2 to triethyl phosphite is 1:(15-30); And / or, the catalyst 3 comprises tetrabutylammonium bromide; And / or, the temperature range of the heating reflux reaction is 150° C. to 200° C.; And / or, the reaction time of the heating reaction is 14h to 20h; and / or, in the crystallization step, adding petroleum ether to the reactant 3; And / or, in the washing step, washing is performed with petroleum ether.

5. The method for preparing the self-assembling small molecule according to claim 2, characterized in that: In the step of preparing the self-assembling small molecule: The molar ratio of the compound 3 to trimethylsilyl bromide is 1:(10-20); And / or, the organic solvent includes at least one of anhydrous 1,4-dioxane, N,N-dimethylformamide, trichloroethane, and tetrahydrofuran; And / or, the reaction time is 20 h to 30 h.

6. A hole transport material, characterized in that The hole transport material comprises the self-assembled small molecule according to any one of claims 1 to 5.

7. A perovskite battery, characterized in that: The perovskite cell comprises a composite hole transport layer, and the composite hole transport layer comprises the hole transport material according to claim 6.

8. The perovskite cell according to claim 7, characterized in that: The preparation method of the composite hole transport layer comprises the following steps: Dispersing a hole transport material in a solvent to obtain a hole transport material dispersion solution, and coating the hole transport layer precursor solution on a surface of a substrate to form a hole transport layer; The self-assembled small molecule according to any one of claims 1 to 6 is dissolved in an organic solvent to obtain a self-assembled small molecule solution, and the self-assembled small molecule solution is coated on the surface of the hole transport layer to obtain the composite hole transport layer.

9. The perovskite battery according to claim 8, characterized in that: The hole transport material includes nickel oxide; and / or the mass concentration of the self-assembled small molecule solution is (0.3-3) mg / mL.

10. The perovskite battery according to claim 8, characterized in that: The hole transport material includes nickel oxide, and the nickel oxide is dispersed in a solvent to obtain a nickel oxide dispersion solution, wherein the mass concentration of the nickel oxide dispersion solution is (10-60) mg / ml.

11. The perovskite battery according to claim 9, characterized in that: The perovskite cell further comprises a perovskite active layer, and the perovskite active layer is arranged on the surface of the composite hole transport layer.

12. The perovskite battery according to any one of claims 7 to 11, characterized in that: The perovskite cell includes an inverted perovskite cell, which includes, from bottom to top, a front electrode layer, a composite hole transport layer, a perovskite active layer, an electron transport layer and a back electrode layer.

Citation Information

Patent Citations

  • Self-assembly hole transport material based on 7H-dibenzocarbazole and synthesis method

    CN115215901A

  • Interface modification material suitable for NiOx layer of trans-perovskite solar cell

    CN117165099A

  • Self-assembly monomolecular layer hole transport material based on naphtho-carbazole core, and preparation method and application of self-assembly monomolecular layer hole transport material

    CN117229319A

  • Self-assembled single-layer material, perovskite solar cell and preparation method of perovskite solar cell

    CN118239978A